Multiple cranial neuropathies secondary to adenoid cystic carcinoma of the parotid gland. Issue 3 (1st April 2022) - Kano, Yuya; Yamada, Kentaro; Muto, Masahiro; Inaguma, Shingo; Yoshida, Mari; Kitamura, Taro; Miura, Toshiyasu; Nakanishi, Hiroki; Mori, Yusuke; Murakami, Shingo; Matsukawa, Noriyuki
Abstract: Multiple cranial neuropathies in adenoid cystic carcinoma (ACC) are rare. We present a patient with a 4‐year history of right peripheral facial nerve palsy, who presented with right mandibular, glossopharyngeal, and vagus nerve impairments. Brain magnetic resonance imaging (MRI) revealed enlargement and contrast enhancement of each cranial nerve and atrophy and abnormal contrast enhancement of the right parotid gland. A parotid gland biopsy led to the diagnosis of ACC. In this case, brain MRI enabled evaluation of the tumor progression pathway invading the cranial nerves. Its results suggested that tumor cells can travel through the cranial nerve anastomotic network, shedding light on the development pattern of tumor cells. It is important to consider the possibility of nerve invasion by ACC as a cause of slowly progressive multiple cranial neuropathies.